Scope International to choose Malaysia based on competitiveness as one of their services hub globally / Amir Ariffin Aminuddin - Aminuddin, Amir Ariffin (Faculty of Business and Management, 2010)
Competitiveness is the ability of a firm or a nation to offer products and services that meet the quality standards of the local and world markets at prices that are competitive and provide adequate returns on the resources employed or consumed in producing them. Many of multinational companies from multiple sectors such as manufacturing, banking, services and others, has selected Malaysia as their outsourcing choices or hub for their business. But why are they preferring Malaysia to be their business Hub or choices? Malaysian has a competitive financial system performs an important intermediation function as well as plays a critical role in promoting economic growth. There are several factors being discovered, like economic stability, political stability, human capital and resources, government policy and others. Scope International (M) Berhad is a subsidiary of Standard Chartered Bank (SCB), and they had chosen Malaysia as one of its hub.